Continuous-Flow Chemistry in the Research Laboratory Modern Organic Chemistry in Dedicated Reactors at the Dawn of the 21st Century - Glasnov, Toma.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a short introduction to the historical background to the field, the state of the art and a brief survey of the available instrumentation and the processing techniques used. The following major areas of interest in synthetic, organic and medicinal chemistry are elaborated on: transition-metal catalyzed reactions, organocatalytic transformations, heterocyclic synthesis, and photochemical reactions. Finally, selected applications in industry are also discussed. With its ample presentation of examples from recent literature, this is an essential and reliable source of information for both experienced researchers and postgraduate newcomers to the field.
Continuous Flow Synthesis - a Short Perspective -- Equipment Overview -- Organic Synthesis in Dedicated Continuous Flow Systems - Transition Metal Catalyzed Carbon-Carbon and Carbon-Heteroatom Bond Forming Reactions -- Organic Synthesis in Dedicated Continuous Flow Systems - Rearrangement Reactions -- Organic Synthesis in Dedicated Continuous Flow Systems - Cycloaddition Reactions -- Organic Synthesis in Dedicated Continuous Flow Systems - Reductions and Oxidations -- Organic Synthesis in Dedicated Continuous Flow Systems - Heterocyclic and Multi-Step Syntheses -- Organic Synthesis in Dedicated Continuous Flow Systems - Synthesis of Radiolabeled Compounds -- Organic Synthesis in Dedicated Continuous Flow Systems - Enzymatic Reactions -- Organic Synthesis in Dedicated Continuous Flow Systems - Further Chemistry Examples -- Outlook.
Keywords: Chemistry, Organic; Microtechnology; Microelectromechanical systems; Chemistry, Technical; Organic Chemistry; Microsystems and MEMS; Industrial Chemistry